Korelasi Antara Debit Aliran dan Sedimen Melayang (Suspended Load) di Sungai Data’ Kabupaten Pinrang - Zulfikar Ali Ahmad; Muh. Nathan; Syamsul Arifin Lias (Universitas Hasanuddin, 2019)
The hydrological process that occurs in a watershed is related to erosion process, sediment transport and downstream deposition. Land use changes and watershed management practices will also affect erosion and sedimentation. The purpose of this study was to determine the magnitude of flowrate, suspended load concentration (suspended load), and floating sediment discharge and correlation of floated sediment discharge and flowrate at the Data’ River. Measuring river characteristics is done by measuring river water flow and river slope. Sediment collection floated with EWI (equal with incerentment) method. Laboratory analysis was carried out by calculating the amount of flow discharge, sediment concentration, and sediment discharge. The results showed the lowest amount of flow discharge occurred on 17/12/2016 with a value of 0.271 m3/s with a floating sediment concentration of 17.167 mg / L, and the sediment discharge floated at 0.402 tons/day. The correlation between flow discharge and floating sediment discharge using a sccatter diagram shows that the determination value R2 is 0.9754 with the equation y = 0.1x + 0.4355.